Corporate Governance and Corporate Social Responsibility Disclosures: Australian and Sri Lankan Market - Pratheepkanth, P. (University of Jaffna, 2021)
This study intends to investigate the effect of corporate governance (CG) on corporate social responsibility (CSR) disclosures of Australian and Sri Lankan listed firms for the period of 2020 to 2016. This study's comparison data comes from 100 Australian (ASX200-listed) firms and 100 Sri Lankan firms (Colombo-stock-exchange-listed firms). A quantitative research strategy employing secondary data is used to answer the study questions. Prior CSR literature was used to develop the checklist. Multiple regression analysis is used in this study to look into the relationship between various governance variables such as board size, board independence, CEO duality and the proportion of female directors, and the extent of CSR disclosures. It was found that the size of the board, board independence, and the number of female directors of the Australian firms have significant effects on the amount of CSR disclosures made than the Sri Lankan firms. CEO duality, on the other hand, appears to be insignificantly related with the degree of CSR disclosures in Australian and Sri Lankan firms, according to the results. This study addresses a gap in the literature by providing comparative study on the influence of CG on CSR disclosures. It also warns regulators, and practitioners in the emerging countries to pay more attention to CG reforms and enforcement, as well as enhance institutional constraints on CSR adaptation.
Keywords: Corporate governance; Board size; Board independence; Corporate social responsibility disclosures